Electromyography for the evaluation of handicapped swimmers - Maes, L.; Clarys, J. P.; Brouwer, P. J. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
In the literature many authors recommend the use of a specific swimming technique for supporting and/or strengthening certain muscles or muscle groups. Very few of these recommendations are based on scientific experiences. Lorenzen (1970) mentioned the strengthening of the extensors of the back during the backcrawl. Vis (1971) indicated the breaststroke was the most effective way to develop the back musculature. According to Duffield (1969) the extensors are generally used in back and front crawl. The flexors are utilized in breaststroke and butterfly. Experimental investigations on the function of muscles during swimming are limited. Ikai et al (1964) compared the electromyogram (EMG) of an Olympic champion with a University champion in breaststroke, front, and back crawl. Lewillie (1968, 1971, 1973) studied the triceps brachii, the biceps brachii, and the quadriceps femoris at different speeds using the four competitive strokes. Clarys et al. (1973) investigated the biceps brachii, the brachia radialis, the flexor carpi ulnaris, and the triceps brachii in subjects executing the front crawl stroke in competition and in water polo. In this study the electrical potentials (EMG) of five preselected muscles were studied during three swimming techniques: a) breaststroke, b) back crawl, and c) front crawl. The results were related to the "normal" and the disabled swimmer.